Water–energy–carbon coupling index assessment of aeration control and techno-economic analysis of hybrid renewable energy for wastewater treatment plant - Intae Shim; Jeongbeen Park; Juwon Lee; Sook-Hyun Nam; Eunju Kim; Jae-Wuk Koo; Tae-Mun Hwang (Journal of Cleaner Production, 2026)

A 20-kyr record of seawater osmium isotope variations in the Okinawa Trough, a marginal basin in the western Pacific: Implications for climate change - Dhongil Lim; Jihun Kim; Juyeon Yang; Sun Min Choi; Intae Kim; Jeongwon Kang; Zhaokai Xu; David Selby (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Spatiotemporal distributions and mass budgets of artificial radionuclides (137Cs and 239,240Pu) in the seas surrounding Korea - Jaeeun Lee; Hyunmi Lee; Intae Kim (Marine Pollution Bulletin, 2026)

First report on the distribution of Acantharia (Radiolaria) in Korean coastal waters: Comparison with their distribution in the northwestern Pacific - Young-Ok Kim; Jungmin Choi; Noritoshi Suzuki; Intae Kim; Jimin Lee (Regional Studies in Marine Science, 2026)

Behaviours of 210Pb and 137Cs in Yellow Sea sediments under the influence of waste dumping - Xiaoyu Chen; Jaeeun Lee; Junhyeong Seo; Hyunmi Lee; Intae Kim (Applied Geochemistry, 2025)

Boundary exchange and benthic fluxes drive trace element cycling in North Pacific marginal seas - Xiaoyu Chen; Hyeryeong Jeong; Kongtae Ra; Huisu Lee; Intae Kim (Limnology and Oceanography, 2025)
Trace elements are essential micronutrients for primary producers in the ocean, supporting vital metabolic functions. However, their behavior in the northwestern Pacific remains unknown. This study investigated the behavior and benthic fluxes of Mn, Fe, Co, Ni, Cu, Zn, and Cd in the East/Japan Sea and the Yellow Sea. Rare earth element fractionations ([Nd/Er] PAAS and Ce/Ce* ratios) were used to trace scavenging and water mass inputs. In the East/Japan Sea, trace element distributions were categorized into three categories. Mn, Fe, and Co were influenced by atmospheric deposition in surface waters and benthic input, with fluxes of 742, 96, and 0.8 μ mol m −2 yr −1 , respectively. Ni and Cu were depleted from surface waters and had a limited influence from benthic inputs. Zn and Cd were regulated by biological activity. Zn concentrations ranged from 0.6 to 1.5 nmol kg −1 at the surface, peaked at 6.8–11.8 nmol kg −1 at a depth of 500 m, and decreased to 3.5–7.9 nmol kg −1 at the bottom. Zn correlated positively with in the upper 500 m but negatively at greater depths, likely owing to shelf inputs. In the Yellow Sea, all trace elements exhibited a vertically conserved distribution owing to rapid water mixing. These results contribute to the current biogeochemical understanding of the region by providing higher‐resolution cross‐transect investigations and report the decoupling of Zn– in the East/Japan Sea for the first time.

Annual distribution and deposition of atmospheric 210Pb in Busan, the largest port city in Korea - Jaeeun Lee; Hyunmi Lee; Jin Young Choi; Ji Hyun Lee; Intae Kim (Journal of Environmental Radioactivity, 2025)

Climate-driven redox changes in the southern Scotia Sea over the last 35 kyr: Insights from sedimentary sulfur isotope - Jihun Kim; Dhongil Lim; Dohyun Jeong; Intae Kim; Haryun Kim; Tae Soo Chang; Kyu-cheul Yoo; Zhaokai Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Particulate organic carbon export fluxes across the Seychelles-Chagos thermocline ridge in the western Indian Ocean using 234Th as a tracer - Junhyeong Seo; Intae Kim; Dong-Jin Kang; Hyunmi Lee; Jin Young Choi; Kongtae Ra; TaeKeun Rho; Kyungkyu Park; Suk Hyun Kim (Frontiers in Marine Science, 2024)
We investigated the export flux of particulate organic carbon (POC) using 234 Th as a tracer in the western Indian Ocean along 60°E and 67°E transects in 2017 and 2018. The Seychelles-Chagos Thermocline Ridge (SCTR), where production is relatively high due to nutrient replenishment by upwelling of subsurface water, was observed at 3°S – 12°S in 2017 and 4°S – 13°S both 60°E and 67°E in 2018. POC fluxes in 2017 showed no differences between the SCTR and non-SCTR regions. However, in 2018, the POC fluxes in the SCTR regions (8.52 ± 7.89 mmol C m –2 d –1 ) were one order of magnitude higher than those observed in the non-SCTR regions (0.63 ± 0.07 mmol C m –2 d –1 ), which appeared to be related to the strong upwelling of subsurface water. These POC fluxes were comparable to those observed under bloom conditions, and thus, are important for estimating the efficiency of carbon sequestration in the ocean.

The Atmospheric Input of Dissolvable Pb Based on the Radioactive 210Pb Budget in the Equatorial Western Indian Ocean - Huisu Lee; Jaeeun Lee; Hyunmi Lee; Intae Kim (Journal of Marine Science and Engineering, 2023)
To estimate the atmospheric deposition flux of 210Pb in the equatorial western Indian Ocean, we determined the dissolved ( 0.45 μm) in the water column. In addition, we calculated the atmosphere-derived dissolvable Pb in seawater using the budget of 210Pb. The dissolved 210Pb and total 210Pb were higher in the surface layer and, overall, showed a decreasing distribution with depth. In particular, radioactive 210Pb activities in the surface-to-upper layer (

Distributions of Radiocesium and Plutonium in the Korean Seas and North Pacific after the Fukushima Accident, 2011–2014 - Jaeeun Lee; Suk Hyun Kim; Huisu Lee; Hyunmi Lee; Intae Kim (Journal of Marine Science and Engineering, 2022)
The distributions of artificial radionuclides, radiocesium (134Cs and 137Cs) and plutonium isotopes (238Pu and 239+240Pu), in the surface water around the Korean seas (East/Japan Sea and Yellow Sea) in 2011–2012 and in three sections in the North Pacific between 2011 and 2014 were examined. The 137Cs activities in the surface water in the Korean seas in 2011 (immediately after the Fukushima nuclear power plant (NPP) accident on 17 March 2011) were comparable or not significantly different relative to those in 2010 and 2012. However, 134Cs, which had been not detected in the study area before the Fukushima accident (under the detection limit of 0.1 mBq kg−1 level), were detected rapidly in 2011 after the accident (in about 60% of the 72 samples) and gradually disappeared due to their short half-life (t1/2 = 2.06 years) in 2012 (detected in about 16% of the 24 samples). In addition, the highest activities of radiocesium and Pu isotopes appeared locally in some stations of the Korean Strait region (located between Korea and Japan) within 1–2 months immediately after the accident. This suggests that the radioactive nuclides released immediately after the Fukushima accident were significantly introduced through the atmosphere, based on recent studies conducted in neighboring areas. We also showed that the spatial distribution of radiocesium in the North Pacific moved eastward from 2012 to 2014, and we attempted to quantify the residence time of radiocesium (137Cs) in the Korean seas based on the long-term (tens of years scale) temporal trends of 137Cs activity data, which have been collected since the 1960s and 1970s. The estimated retention time of 137Cs in the East/Japan Sea and Yellow Sea were 25 ± 0.6 and 8.0 ± 0.1 years, respectively. These results are expected to be used as a preliminary study for a potential future event of a marine radioactive accident (which, of course, cannot be predicted) and as basic data for predicting the influences of radionuclide releases in the ocean.

Dissolved Pb Concentrations and Stable Pb Isotope Ratios in the Ulleung Basin, East/Japan Sea - Seonghu Choi; Man-Sik Choi; Dongjin Joe; Sojung Park; Jinwoo Kim; Kongtae Ra; Intae Kim; Kyung-Tae Kim; Kyoung-Seok Lee; Jean-Sun Lim (Ocean Science Journal, 2022)

Tracing the Atmospheric Input of Seawater-Dissolvable Pb Based on the Budget of 210Pb in the East Sea (Japan Sea) - Hojong Seo; Guebuem Kim; Young-Il Kim; Intae Kim (Frontiers in Marine Science, 2021)
In order to determine the atmospheric input of 210 Pb and seawater-dissolvable Pb in the East Sea (Japan Sea), we measured the concentrations of total 210 Pb and dissolved Pb (<0.2 μm) in seawater and 210 Pb and 226 Ra in sinking particles. The East Sea is deep (∼3700 m) and enclosed by surrounding continents except for the shallow sills (<150 m). Since the East Sea is located off the East Asian continent under the westerlies, the concentrations of 210 Pb and dissolved Pb in this sea are significantly affected by terrestrial sources through the atmosphere. The vertical profiles of total 210 Pb and dissolved Pb generally showed a surface maximum and then decreased with depth. The concentrations of dissolved Pb in the surface water were 2 and 3 times higher than those in the North Pacific and North Atlantic Oceans, respectively. Using an independent box model (upper 1000 m or 2000 m), we estimate the atmospheric input of 210 Pb to be 1.46 ± 0.25 dpm cm −2 y − 1 , which is within the range of published results from the land-based sites (0.44–4.40 dpm cm −2 y − 1 ) in South Korea, China, and Japan. Based on this flux, the residence time of total 210 Pb in the East Sea is calculated to be approximately 7.1 ± 1.6 years, which is twice lower than the previous estimation. Combining the residence time of 210 Pb and the inventory of dissolved Pb, the atmospheric input of seawater-dissolvable Pb is estimated to be 0.98 ± 0.28 nmol cm −2 y − 1 . This flux is approximately 25% of the Pb flux through the wet deposition (acid-leachable fraction). Thus, our results suggest that the flux and fate of atmospheric Pb in the ocean can be successfully determined using an accurate mass balance model of naturally occurring 210 Pb.

R/V Isabu-Based First Ultraclean Seawater Sampling for Ocean Trace Elements in Korea - Suk Hyun Kim; Kongtae Ra; Kyung-Tae Kim; Hyeryeong Jeong; Jihyun Lee; Dong-Jin Kang; Taekeun Rho; Intae Kim (Ocean Science Journal, 2019)